Quantum and classical effects in scattering of relativistic electrons by crystal atomic string - Shul’ga, N.F.; Truten', V.I. (Вопросы атомной науки и техники, 2001)
The results of investigation of the relativistic electron scattering by a crystal atomic string at a small incident angle to its axis are presented. The possibility of the particle rainbow scattering and orbiting in this case is shown. It is shown that the Ramsauer-Townsend-type effect of the total cross-section decrease for elastic scattering of relativistic electrons by a crystal atomic string can take place at small values of particle incidence angles.